Run length properties of run rules EWMA chart using integral equations. Issue 2 (4th March 2019) - Maravelakis, Petros E.; Castagliola, Philippe; Khoo, Michael B. C.
Abstract: The EWMA chart is a control chart that is able to quickly detect small to moderate shifts in the process mean. Runs rules is a popular technique in the area of control charts that are used to improve the performance of the standard Shewhart control chart for the mean. Recently, several researchers investigated the performance of EWMA type control charts incorporating runs rules using either simulation or Markov chains. As these methods only yield approximate results, in this paper, we present an exact approach based on integral equations for studying the run length performance of the EWMA control chart with runs rules.